Culture of standardization - García Pantigozo, Manuel (1998)
The culture of standardization has become a competitive advantage; develop those who will survive, and those who do not, will be isolated in the market. Have been established quality standards (ISO 9000), environmental (ISO 14000), on laboratory accreditation (ISO 25) on food (HACCP) and drugs (NCF).